Analisis Yuridis Tindak Pidana Perjudian Bola Guling (Studi Kasus Berdasarkan Berita Acara Pemeriksaan Saksi Dari Laporan Polisi No. Pol.: Lp/A/K/02/X/2025/Sat Reskrim/Polres Belu) - Finsensius Samara; Hilarianti G.S Nahak; Suzanthyka M.C Ballo; Serafina J. Taneo; Maria P.F Asten; Kasumi Matsushita; Alexandro G.E.M Maya (SENTRI: Jurnal Riset Ilmiah, 2026)
Gambling is one of the most frequently encountered crimes in society, both through print and electronic media, and in everyday activities. There are numerous motives behind gambling crimes. Gambling crimes are usually motivated by the perpetrator's daily life circumstances, such as economic circumstances or a low income that makes it impossible to cover daily living expenses, as well as a low level of education. One fact that cannot be ignored is that, in some cases, gambling crimes are often "rigged" with other forms of crime, namely by becoming an "enterprise" or illegal livelihood. The goal is clear: to ensure that the gambling activity proceeds according to the perpetrator's plan, by profiting from the bets. The greater the profit, the greater the perpetrator's opportunity to make the activity a livelihood. This analysis examines a case of ball rolling gambling, regulated under Article 303 of the Indonesian Criminal Code, based on the Witness Examination Report from Police Report No.: LP/A/K/02/X/2025/SAT RESKRIM/Polres Belu.